2013
DOI: 10.1016/j.atherosclerosis.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-derived eicosanoids and vascular dysfunction in coronary artery disease patients

Abstract: Objective Accumulating preclinical and epidemiologic evidence has emerged to suggest that modulation of cytochrome P450 (CYP)-mediated eicosanoid metabolism may be a viable vascular protective therapeutic strategy for the secondary prevention of coronary artery disease (CAD). The functional relationship between CYP-derived eicosanoid metabolite levels and vascular dysfunction in humans with established CAD, however, has not been evaluated. Therefore, we characterized the relationship between inter-individual v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 30 publications
1
54
0
Order By: Relevance
“…protein 1 (MCP-1) concentrations [a proinfl ammatory chemokine predictive of poor prognosis in CAD ( 43 )], in which patients with stable CAD in the lowest and middle EET tertiles had signifi cantly higher MCP-1 levels compared with those in the highest EET tertile ( 18 ). These preliminary observations underscore the need to rigorously evaluate the relationship between EET levels and the risk of cardiovascular events in larger populations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…protein 1 (MCP-1) concentrations [a proinfl ammatory chemokine predictive of poor prognosis in CAD ( 43 )], in which patients with stable CAD in the lowest and middle EET tertiles had signifi cantly higher MCP-1 levels compared with those in the highest EET tertile ( 18 ). These preliminary observations underscore the need to rigorously evaluate the relationship between EET levels and the risk of cardiovascular events in larger populations.…”
Section: Discussionmentioning
confidence: 90%
“…The sum EETs served as the primary end point for comparison across CAD extent. The sum of the EET and DHET regioisomers (sum EETs + DHETs) and the ratio of 14,15-EET to 14,15-DHET (14,15-EET:14,15-DHET ratio) (secondary end points) were calculated as biomarkers of CYP epoxygenase and sEH metabolic function, respectively ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies (36,37) have shown increased 20-HETE levels in hypertensive individuals. A recent study by Schuck et al (27) demonstrated that enhanced plasma levels of 20-HETE are associated with more advanced endothelial dysfunction and vascular inflammation in patients with established atherosclerotic cardiovascular disease. The proinflammatory and progrowth bioactions of 20-HETE in vascular cells together with its increased occurrence in hypertensive patients suggest that it may play a role in microvascular remodeling and contributes to the development and cardiovascular complications of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The hyperpolarization of smooth muscles and vasodilation induced by EETs are mediated by activation of Ca 2+ -dependent K + channels, with stronger cardioprotection leading to activation of K(ATP) channels. 29) Considering that EET concentrations and the 14,15-EET/14,15-DHET ratio in plasma have negative correlations with the risk of cardiovascular events, 30,31) a decrease of the EETs concentration in patients taking ARBs would correlate with an increase risk of cardiovascular events including sudden cardiac death and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%